DECENTRALIZED FINANCE (DeFi) AND ITS IMPLICATIONS FOR MONETARY POLICY EFFECTIVENESS IN DEVELOPING COUNTRIES - M. Fakhriansyah; Kurnia Ramadhon (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to examine the impact of Decentralized Finance (DeFi) on the effectiveness of monetary policy in developing countries through a literature review approach. DeFi, as a blockchain-based financial system that operates without traditional intermediaries, is increasingly demonstrating its potential to disrupt conventional monetary policy transmission mechanisms. Through an analysis of various academic studies, reports from international financial institutions, and recent publications on DeFi dynamics, this study identifies the key challenges faced by central banks in maintaining price stability, managing liquidity, and regulating the financial system amidst the widespread use of digital assets and DeFi protocols. Furthermore, DeFi also offers opportunities to increase financial inclusion and payment system efficiency, particularly in developing countries facing limitations in traditional financial infrastructure. The study's findings suggest that the success of monetary policy in the digital era depends heavily on the ability of monetary authorities to respond to technological innovation through policy adaptation, dynamic regulation, and cross-sector collaboration. This study provides a conceptual contribution to understanding the interaction between decentralized financial innovation and traditional macroeconomic instruments in the context of developing countries.